Modelling as intervention technology: Science, politics, and water conflicts - Ehsan Nabavi (Water Alternatives)
In water conflicts, models and their creators are often seen as guides that help public and policy actors make sense of controversies and formulate responses. In such contexts, it is tempting for both modellers and decision-makers to adopt the narrative that models are neutral and that, by extension, they present objective insights. This assumption, however, overlooks two critical issues. First, many choices made by modellers, which significantly shape a model’s outcome, are subjective and context-dependent. Second, water conflicts are inherently sociopolitical processes, and models themselves actively shape how these conflicts unfold. This paper argues that within hydropolitical dynamics, water models become the 'focal points' of a convergence of scientific expertise, political priorities and societal values and expectations. They become 'intervention technologies' that actively shape the very water realities they seek to describe. Drawing on ethnographic research and on insights from Science and Technology Studies, this paper explores this argument through the case of a water transfer controversy in the Zayandeh-Rood River Basin in central Iran. By unpacking how modelling (and countermodelling) practices are entangled with broader sociopolitical dynamics, the paper traces how models intervene in the making of the common resource, common sense and common good, while themselves being in turn shaped by these contested arenas.